The Development Of B-Pro Detect (Brainstorming, Problem Identification, Prototype Design, Try, Conflict Evaluation) Learning Model to Increase Creative Thinking and Learning Results of SMP/MTs Students - Maghfiroh, Siti Nuriga; Prihatin, Jekti; Handayani, Rif’ati (BIOEDUKASI, 2024)
Education has undergone significant changes in modern times. Students are experiencing a decline in their thinking skills, particularly in the areas of creativity and critical thinking. This is due to the monotonous nature of their learning, which has resulted in less developed thinking patterns. The EDP model aims to improve creative problem-solving skills, equip students with the ability to overcome difficulties through careful planning, and encourage learning through failure. This study describes the B-ProDe TEct (Brainstorming, Problem Solving, Design Prototype, Try, Evaluate of Conflicts) learning model, which integrates Brain-Based Learning (BBL) principles into Engineering Design Process (EDP). The model has been demonstrated to enhance creative thinking skills and improve science learning outcomes in junior high school students. The study utilizes a mixed methods research approach, combining both quantitative and qualitative methods. This approach enables a more comprehensive analysis of the research question. The practicality scores from each school, derived from the feasibility test, were 87.08%, 83.25%, and 86.67% respectively, resulting in an overall average of 85.67%. The study evaluated the effectiveness of the B-Pro DeTEct learning model on a group of 30 students. The N-gain was 0.37 at the third session and 0.55 at the fourth session, with an average N-gain of 0.46. These results suggest a moderate increase in cognitive learning outcomes before and after using the model. The study concludes that the model is valid, practical, and successful in enhancing creative thinking skills.